دراسة بعض مؤشرات إنتاجية البيض, وعمر النضج الجنسي عند الجيل الثاني (F2) المنتخب لدى الدجاج البلدي السوري في البيئة الساحلية - حميشة محسن; جلنكريان بيرنا (Latakia University Journal -Biological Sciences Series, 2019)
نفذ البحث خلال عامي 2009-2010, ودرست فيه مؤشرات عمر النضج الجنسي وكمية (عدد) البيض, وزن البيض وإنتاجية البيض خلال 150 يوماً عند 169 دجاجة بلدية محلية تنتمي إلى الجيل الثاني F2 المنتخب من قطيع آباء الجيل الأول F1. وأظهرت نتائج البحث: - أن عمر النضج الجنسي بلغ 195 يوماً. - وأن كمية البيض خلال الفترة المدروسة عند كامل قطيع التجربة بلغت 86,94 بيضة بمتوسط شهري قدره 17,39 بيضة, ووصلت عند الدجاجات المنتخبة لإنتاج F3 99,59 بيضة بمتوسط 19,92 بيضة شهرياً. - أما متوسط وزن البيضة عند كامل قطيع التجربة فقد بلغ 49,75 غراماً وعند الدجاجات المنتخبة فكان 50,29 غراماً. - وبلغ متوسط إنتاجية البيض عند قطيع التجربة 0,58 بيضة/دجاجة/يوم بينما بلغ هذا المتوسط عند الدجاجات المنتخبة 0,66 بيضة/دجاجة/يوم. A research experiment was conducted throughout 2009-2010 season. The research studied during 150 days the indicators of the sexual maturity age and the egg quantity, weight and productivity of 169 local hens belonging to the second generation F2 selected from the first generation flock F1. The research results indicated that: · The age of sexual maturity was 195 days. · The egg quantity during the studied period of the whole studied flock was 86,94 eggs with a monthly average of 17,39 eggs, while it was 99,59 eggs in the selected hens for producing F3 with a monthly average 19,92 eggs. · The egg weight average of the whole experiment flock was 49,75 g, while the average of the selected hens was 50,29 g. · The egg productivity average of the whole experiment flock was 0,58 egg/hen/day, while it was 0,66 egg/hen/day in the selected hens.